Due to the Law for the Making of a Power of Power of sell which is Not Previous with the Principal Agreemtent in the Transaction of the Selling of Inspired Land (Case Study of Ma Decision No. 772/K/Pdt/2018) - Nynda Fatmawati Octarina; Edith Edith (Budapest International Research and Critics University, 2022)
This study discusses the legal consequences of making a power of attorney to sell which is not preceded by a principal agreement in the sale of inherited land. This research is a normative juridical law research with qualitative methods to analyze data and descriptive analytical research type. Power of attorney to sell is a form of special power of attorney. Where in the Special Power of Attorney it must be stated clearly and unequivocally regarding what legal actions and actions may be taken by the Proxy. This is so that the power of attorney does not deviate from the intent of the Authorizer. Power of attorney to sell is a form of accessoire agreement. Accessoir agreement is an additional agreement that follows the Principal Agreement. Power of attorney to sell that stands alone without following the main agreement, it is very risky for deviations to occur in its implementation. This is because the power of attorney to sell which stands alone usually does not include the rights and obligations of the giver and Power of Attorney in detail, clearly, firmly.